203 ELN Gene: UKGTN Service for SVAS and Cutis Laxa. Copy Number Variants (CNVS) Are a Common Cause of Disease. (3rd June 2016) - Gable, Mary; Burton-Jones, Sarah; Turner, Claire; Dean, John; Constantinou, Panayiotis; Scurr, Ingrid; Low, Karen; Wakeling, Emma; Newbury-Ecob, Ruth; Williams, Maggie
Abstract : Pathogenic ELN gene mutations ( ELN, MIM#130160) cause AD Supravalvular Aortic Stenosis (SVAS) a congenital narrowing of the ascending aorta, and Cutis Laxa (CL) characterised by inelastic, loose-hanging skin. Variable phenotype and penetrance is apparent. Pathogenic ELN variants result in loss of function and include frameshift (most common), nonsense, splice site and missense variants. The well characterised contiguous gene deletion syndrome, Williams-Beuren syndrome includes SVAS and encompasses at least 114kb on 7q11.23 including the ELN gene; however, there are only 5 case reports of CNVs within ELN (single or multiple exons). Bristol Genetics Laboratory provides a UKGTN approved service for ELN gene sequencing (33 coding exons). In three years, 52 UK and foreign patients with SVAS, CL or features such as pulmonary artery stenosis and aortic dilation have been tested. 18/52 (34%) patients were heterozygous for a likely pathogenic variant including frameshift (6), nonsense (4), splice (4), and missense (4). 12 of these cases were novel variants, 5 are supported by segregation analysis and 1 is sporadic. The remaining novel variants are classed as possibly pathogenic as they are phenotypically compatible. 12/35 patients negative on sequencing have so far been screened for CNVs by MLPA (MRC Holland) covering the Williams-Beuren syndrome region, including 10 exons of the ELN gene (1,  3,  4,  6,  9,  16,  20, 26, 27 and 33) and in addition a bespoke MLPA assay including probes for exons 28 to 30, 32 and 3'UTR. 4/12 (33%) patients have a heterozygous deletion within the ELN gene. A mother and daughter with pulmonary stenosis and an extended family history have a deletion spanning exons 30 to 33. This deletion was also identified in another patient with SVAS and arteriopathy. A deletion of the 5' end of the gene, involving at least exon 1 (but not exon 3) was identified in an infant with SVAS and pulmonary branch stenosis, and a deletion involving the entire coding region of the ELN gene and at least the first two exons of the adjacent 3' gene LIMK1 was detected in a neonate who died at 2 months with SVAS, pulmonary stenosis and mild hypoplasia with PDA. The deletion was detected in this patient's father who consequentially was found to have an aortic regurgitation and in a subsequent pregnancy of this family which was lost at 31 weeks with pulmonary stenosis and significant aortic stenosis MLPA analysis has enhanced the clinical utility of this service giving an increased diagnostic yield in patients with SVAS and CL and related presentations.